Escherichia coli O104 in Feedlot Cattle Feces: Prevalence, Isolation and Characterization - Shridhar, Pragathi B.; Noll, Lance W.; Shi, Xiaorong; Cernicchiaro, Natalia; Renter, David G.; Bai, Jianfa; Nagaraja, Tiruvoor G. (My University, 2016)
Escherichia coli O104:H4, an hybrid pathotype of Shiga toxigenic and enteroaggregative E. coli, involved in a major foodborne outbreak in Germany in 2011, has not been detected in cattle feces. Serogroup O104 with H type other than H4 has been reported to cause human illnesses, but their prevalence and characteristics in cattle have not been reported. Our objectives were to determine the prevalence of E. coli O104 in feces of feedlot cattle, by culture and PCR detection methods, and characterize the isolated strains. Rectal fecal samples from a total of 757 cattle originating from 29 feedlots were collected at a Midwest commercial slaughter plant. Fecal samples, enriched in E. coli broth, were subjected to culture and PCR methods of detection. The culture method involved immunomagnetic separation with O104-specific beads and plating on a selective chromogenic medium, followed by serogroup confirmation of pooled colonies by PCR. If pooled colonies were positive for the wzx(O104) gene, then colonies were tested individually to identify wzx(O104)-positive serogroup and associated genes of the hybrid strains. Extracted DNA from feces were also tested by a multiplex PCR to detect wzx(O104)-positive serogroup and associated major genes of the O104 hybrid pathotype. Because wzx(O104) has been shown to be present in E. coli O8/O9/O9a, wzx(O104)-positive isolates and extracted DNA from fecal samples were also tested by a PCR targeting wbdD(O8/O9/O9a), a gene specific for E. coli O8/O9/O9a serogroups. Model-adjusted prevalence estimates of E. coli O104 (positive for wzx(O104) and negative for wbdD(O8/O9/O9a)) at the feedlot level were 5.7% and 21.2%, and at the sample level were 0.5% and 25.9% by culture and PCR, respectively. The McNemar's test indicated that there was a significant difference (P < 0.01) between the proportions of samples that tested positive for wzx(O104) and samples that were positive for wzx(O104), but negative for wbdD(O8/O9/O9a) by PCR and culture methods. A total of 143 isolates, positive for the wzx(O104), were obtained in pure culture from 146 positive fecal samples. Ninety-two of the 143 isolates (64.3%) also tested positive for the wbdD(O8/O9/O9a), indicating that only 51 (35.7%) isolates truly belonged to the O104 serogroup (positive for wzx(O104) and negative for wbdD(O8/O9/O9a)). All 51 isolates tested negative for eae, and 16 tested positive for stx1 gene of the subtype 1c. Thirteen of the 16 stx1-positive O104 isolates were from one feedlot. The predominant serotype was O104:H7. Pulsed-field gel electrophoresis analysis indicated that stx1-positive O104:H7 isolates had 62.4% homology to the German outbreak strain and 67.9% to 77.5% homology to human diarrheagenic O104:H7 strains. The 13 isolates obtained from the same feedlot were of the same PFGE subtype with 100% Dice similarity. Although cattle do not harbor the O104:H4 pathotype, they do harbor and shed Shiga toxigenic O104 in the feces and the predominant serotype was O104:H7.
Citation: Shridhar, P. B., Noll, L. W., Shi, X. R., Cernicchiaro, N., Renter, D. G., Bai, J., & Nagaraja, T. G. (2016). Escherichia coli O104 in Feedlot Cattle Feces: Prevalence, Isolation and Characterization. Plos One, 11(3), 17. doi:10.1371/journal.pone.0152101
Keywords: Virulence Genes; Multiplex Pcr; Intimin Types; Outbreak; Strains; Identification